2014
DOI: 10.5194/acp-14-12393-2014
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate model assessment of the urban land-surface forcing over central Europe

Abstract: Abstract. For the purpose of qualifying and quantifying the climate impact of cities and urban surfaces in general on climate of central Europe, the surface parameterization in regional climate model RegCM4 has been extended with the Single-layer Urban Canopy Model (SLUCM). A set of experiments was performed over the period of 2005-2009 for central Europe, either without considering urban surfaces or with the SLUCM treatment. Results show a statistically significant impact of urbanized surfaces on temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 85 publications
7
55
0
1
Order By: Relevance
“…It indicates a negative model bias, which is highest in spring (around −1 to −2 K over large areas) and lowest in summer (0 to −1.5 K). This is attributable to overestimated cloudiness in RegCM, as already concluded by Huszar et al (2014), who used the same model and set-up. Over mountainous areas like the Alps, southeastern Carpathians, biases reach values from −5 to 5 K, however, this is most probably related to coarse model representation of specific terrain features (valleys, ridges etc.)…”
Section: Model Validationmentioning
confidence: 51%
See 3 more Smart Citations
“…It indicates a negative model bias, which is highest in spring (around −1 to −2 K over large areas) and lowest in summer (0 to −1.5 K). This is attributable to overestimated cloudiness in RegCM, as already concluded by Huszar et al (2014), who used the same model and set-up. Over mountainous areas like the Alps, southeastern Carpathians, biases reach values from −5 to 5 K, however, this is most probably related to coarse model representation of specific terrain features (valleys, ridges etc.)…”
Section: Model Validationmentioning
confidence: 51%
“…In this study, the BATS scheme is activated. The single layer urban canopy model coupled to RegCM4.2 introduced by Huszar et al (2014) was not applied assuming that the urban-meteorological influence on the emissions impact will be minor and furthermore, to meet the computational demand of long climate simulations.…”
Section: Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations of winter weather conditions and air quality for central and southeastern Europe by [23] demonstrated that climate change will be followed by deteriorated air quality, not only due to potentially increased O 3 concentrations, but also as a result of an expected growth in SO 2 concentration levels, with relatively low changes in PM 10 concentrations. Methods for tackling these negative trends include restructuring of urban space and amelioration of the tropospheric climate of the city.…”
Section: Introductionmentioning
confidence: 99%